Removal of contaminants in a paper mill effluent by Azolla caroliniana - D. Sivakumar; J. Nouri (Global Journal of Environmental Science and Management)
This study was focused on removal of various parameters in paper mill effluent using a method called bioremediation by Azolla caroliniana.  The experimental investigations have been carried out using Azolla caroliniana for conducting the sorption study with various dilution ratios (2, 4, 6, 8, and 10), pH (3, 4, 5, 6, 7, 8 and 9) and biomass (200, 400, 600, 800 and 1000 g). The maximum removal percentage of TDS, BOD and COD in a paper mill effluent was obtained at the optimum dilution ratio of 6, pH of 8 and biomass of 800 g. The results of this study indicated that the maximum removal percentage of TDS, BOD and COD in a paper mill effluent was 82.3 %, 88.6 % and 79.1 % respectively.  Also, the study focused on uptake of TDS, BOD and COD in paper mill effluent by Azolla caroliniana through bioaccumulation factor and translocation factor. The results of bioaccumulation factor revealed that TDS, BOD and COD in paper mill effluent were adsorbed by Azolla caroliniana.  The results of translocation factor revealed that the roots of Azolla caroliniana translocate the TDS, BOD and COD in a paper mill effluent to the shoots of Azolla caroliniana. From the results, this study concluded that bioremediation by Azolla caroliniana could be effectively used for removing TDS, BOD and COD in a paper mill effluent. This study also suggested that Azolla caroliniana may be used for removing various contaminants, not only from paper mill effluent, but also from any other industrial effluents.